Strategi Bisnis UMKM dalam Meningkatkan Penjualan (Studi pada Industri Kreatif UMKM Desa Kebonagung Kecamatan Sukodono) - Arifianti, Maudy Nur; Ashar, Muhammad; Prasetyo, Indra Wahyu; Sujatmoko, Didit; Wilujeng, Fitri Dian; Rahmadani, Muhammad; Rahmawati, Imelda Dian (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to analyze the business strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) in Kebonagung Village, Sukodono Subdistrict, to enhance their product sales. The research background highlights the importance of economic development based on local potential and innovation, as well as the challenges faced by MSMEs, such as limited capital, facilities, and human resources. The study employed a qualitative method with in-depth interviews conducted with 30 MSME entrepreneurs. The results indicate that the MSME entrepreneurs applied three generic business strategies according to Michael E. Porter: Differentiation Strategy, Low-Cost Strategy, and Focus Strategy. The differentiation strategy was implemented by creating unique and high-quality products, while the low-cost strategy focused on setting competitive prices. Additionally, the focus strategy aimed at understanding and meeting the needs of specific market segments. Efforts to increase sales were carried out through product innovation, market research, and setting clear sales targets. The study concludes that the appropriate implementation of business strategies can assist MSMEs in Kebonagung Village in increasing sales and achieving business sustainability